2017
DOI: 10.1016/j.jagp.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Prevalence of Hoarding and Obsessive Compulsive Disorder: A Population-Based Study

Abstract: Objectives Little is known about the age-specific prevalence of hoarding and obsessive compulsive (OC) symptoms, particularly in older age groups. The objectives of this study were to estimate the age-specific prevalence, severity and relationships between hoarding and OC symptoms in males and females using a large population-based sample. Methods We assessed the age-specific prevalence rates of hoarding disorder (HD) and obsessive compulsive disorder (OCD) in males and females (at various age ranges between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 66 publications
3
59
1
5
Order By: Relevance
“…The onset of hoarding symptoms, whether in the context of hoarding symptoms or HD, is most likely to occur prior to age 20 years [36,38,40] , which is consistent with the typical age of onset of OCD [41] . However, in contrast to the typical cyclical course of OCD symptoms across the lifespan [42] , hoarding symptoms are likely to be chronic [36] and progressive over the lifespan [36,40,43] . One recent study indicated that the prevalence of provisional HD diagnoses increased steadily by 20% with every 5 years of age [43] .…”
Section: Agementioning
confidence: 99%
See 2 more Smart Citations
“…The onset of hoarding symptoms, whether in the context of hoarding symptoms or HD, is most likely to occur prior to age 20 years [36,38,40] , which is consistent with the typical age of onset of OCD [41] . However, in contrast to the typical cyclical course of OCD symptoms across the lifespan [42] , hoarding symptoms are likely to be chronic [36] and progressive over the lifespan [36,40,43] . One recent study indicated that the prevalence of provisional HD diagnoses increased steadily by 20% with every 5 years of age [43] .…”
Section: Agementioning
confidence: 99%
“…However, in contrast to the typical cyclical course of OCD symptoms across the lifespan [42] , hoarding symptoms are likely to be chronic [36] and progressive over the lifespan [36,40,43] . One recent study indicated that the prevalence of provisional HD diagnoses increased steadily by 20% with every 5 years of age [43] . Specifically, difficulty discarding appeared to account for increases in HD diagnoses with age [43] .…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…20 Em estudo conduzido na Holanda, a prevalência de TA foi de 2,12% em ambos os sexos, com aumentos lineares em torno de 20% a cada 5 anos. 21 Em nosso meio, um estudo transversal realizado em Curitiba (PR) sobre a frequência de comportamento acumulador mostrou uma taxa O TA está associado a comorbidades psiquiátricas, incluindo taxas elevadas de depressão, transtorno de ansiedade generalizada (TAG), fobia social, transtorno de déficit de atenção e hiperatividade (TDAH) e TOC. 5 Nos idosos com TA, especificamente, as comorbidades mais frequentes são depressão (14-54%), transtornos de ansiedade, transtornos de personalidade, transtorno de estresse pós-traumático e transtornos relacionados ao uso de substâncias.…”
Section: Acumulação "Orgânica"unclassified
“…Entretanto, segundo estudo recente, as taxas de prevalência em idosos ultrapassam 6%, de modo que não parece haver diferença entre os gêneros. 6 A evidência sugere que a gravidade dos sintomas de acúmulo aumenta com a idade. 1 O comportamento de acumulação em idosos foi observado concomitantemente às seguintes condições: transtornos de ansiedade, depressivos, de personalidade, de estresse pós-traumático e do uso de substâncias, sendo as duas primeiras as mais frequentemente relatadas.…”
Section: Introdução E Objetivounclassified